Role of MLIP in burn-induced sepsis and insights into sepsis-associated cancer progression - Li, Zhiwei; Wang, Qian; Liu, Yezi; Yang, Shuting; Zhao, Jin; Wu, Changdong; Wang, Changmin (Frontiers in Immunology, 2025)
IntroductionBurn-induced sepsis is a critical clinical challenge marked by systemic inflammation, immune dysregulation, and high mortality. Macrophage-driven inflammatory pathways are central to sepsis pathogenesis, while immune cell metabolic reprogramming plays a key role in both sepsis and cancer progression.MethodsBioinformatics analyses using GEO, TCGA, and GTEx datasets identified MLIP-modulated genes linked to immune responses and prognosis. In vitro, LPS-stimulated HUVEC cells were used to study MLIP’s effects on inflammation and macrophage function through cell viability, ROS levels, cytokine expression, qRT-PCR, and immunofluorescence assays.ResultsMLIP-modulated genes were associated with immune-related metabolic pathways in both sepsis and cancer. Epigenetic analysis showed MLIP expression is regulated by promoter methylation and chromatin accessibility. Prognostic analyses revealed MLIP’s impact on survival outcomes across cancer types. In vitro, MLIP reduced inflammation, oxidative stress, and macrophage hyperactivation.ConclusionsMLIP regulates immune-metabolic dynamics in burn-induced sepsis, influencing macrophage activity and oxidative stress. Its role in metabolic reprogramming suggests MLIP as a potential therapeutic target linking immune modulation and cancer progression. Further research on MLIP’s role in immune evasion and tumor metabolism may inform novel therapeutic strategies.